Self-Repair as Students Development-Oriented Self Assessment in Oral Performance - Trisanti, Novia (Language Circle: Journal of Language and Literature, 2017)
There are certain concerns that a teacher needs to observe in assessing students oralperformance, such as the amount of words, the grammatical errors, the hesitation and certain expression. This paper attempts to give overview of research results using qualitative method which show the impacts of self repair typeanalysis as development- oriented self-assessment in oral performance. The subject was the tertiary level learners of English Department, Universitas Negeri Semarang, Indonesia in 2016. They performed the speaking tasks oraly in Speaking For General Purposes class. They were given the modified rubric of oral performance including the aspects of self-repairs and asked to evaluate their own performance (selfassessment). They were introduced by the term of self-repairs in simple manner and they were instructed to give self and other repairs whenever they needed in their perfomances.All the spoken data were recorded. Concerning the repair types, there are two self-repairs as reviewed by Buckwalter (2001) which occured in self-assessment, they are Self-Initiated Self Repair (SISR), and Self-Initiated Other Repair (SIOR). The finding showed that SIOR occured 60% of all the repairs in students‘ conversation. Then, it could be as development-oriented self-assessment which can be a valuable additional means to improve students speaking since it is one of the motives that drive self- evaluation, along with self- verification and self- enhancement.Also, this development- oriented self-assessment began to receive attention as the result of increasing interest in the learners- centered approach. The results are hoped to give beneficial implication on student‘s oral performance assessment.